Atmospheric Rivers and precipitation in the Madeira Island: 10-years analysis - Couto, Flavio (2015)
The purpose of this work is to bring more evidence about the Atmospheric Rivers (ARs) occurrence in the North Atlantic Ocean (NAO) and their relationship with significant precipitation in the Madeira Island during 10 winter seasons. In this study, the meridional water vapor transport associated to the ARs is visually identified from total precipitable water field extracted from the Atmospheric Infrared Sounder (AIRS) data. The IPMA national meteorological network of Madeira surface stations provide the precipitation data over the island used here. The detection of long and narrow moisture plumes associated with ARs that passed over Madeira, between winter 2002/2003 and winter 2011/2012, is made over a domain covering the NAO (latitudes between 10°N and 60°N and longitudes between 5°E and 100°W). The image analysis show that moist air emanating mainly from the Caribbean Sea and central region of the Tropical Atlantic may flow northward or eastward, usually in the form of a narrow band with an intense horizontal gradient of precipitable water, and throughout the winter periods. However, large part of these filamentary structures intersects the Madeira Archipelago in a dissipating stage. In addition, the analysis also allowed for the development of a conceptual model related to this meridional transport passing over the island.